Performing best when it matters the most: Evidence from professional handball - Christoph Bühren; Marvin Gabriel (Philipps-University Marburg, School of Business and Economics, 2021)
We analyze the impact of psychological pressure on individual performance with handball penalties thrown in the decisive stage vs. the rest of the game. Contrary to the phenomenon of choking under pressure, we observe that most of the analyzed players perform best when it matters the most. The positive effect of pressure on performance is especially pronounced when the score is level or when the thrower's team is lagging. We control for gender and psychological traits assessed with a survey. Female players score with a higher probability than male players in our sample. The positive impact of pressure is not significantly higher for female players.
Keywords: D; 91; 330; Performance under pressure; sports data; psychological traits; survey